2017
DOI: 10.1177/0972262917700991
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Environmental Attitude and Willingness to Purchase Environmentally Friendly Products: An SEM Approach

Abstract: It has been found that in spite of showing concern for the environment and advocating environmentally safe activities, the Indian consumer is still not ready to accept the hard truth that it the responsibility of one and all to minimize their contribution to the overall environmental pollution. This article aims at studying socio-psychological factors which contribute in the formation of environmental attitude of consumers. It further aims at establishing the connection between environmental attitude of the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 41 publications
(49 reference statements)
5
27
0
Order By: Relevance
“…As all the scores of McDonald ω are above 0.6, it can be conferred that the measurement scale meets composite reliability criteria. Further on, it supports the convergent validity of all the four sub-constructs of the research model based on composite reliability as well (Malik and Singhal, 2017). Two indirect items related to variable “time taken to buy organic food vs. non-organic food” were removed, as it had a very low inter-rest correlation in PBC sub-construct, to improve reliability.…”
Section: Methodssupporting
confidence: 60%
“…As all the scores of McDonald ω are above 0.6, it can be conferred that the measurement scale meets composite reliability criteria. Further on, it supports the convergent validity of all the four sub-constructs of the research model based on composite reliability as well (Malik and Singhal, 2017). Two indirect items related to variable “time taken to buy organic food vs. non-organic food” were removed, as it had a very low inter-rest correlation in PBC sub-construct, to improve reliability.…”
Section: Methodssupporting
confidence: 60%
“…Further, green purchase intention may act as a mediator between green consumption value and green consumer behaviour (Hauser et al, 2013). Studies show that green purchase intention acts as a mediator between consumer attitude and green consumer behaviour (do Paço et al, 2019; Jaiswal & Kant, 2018; Malik & Singhal, 2017; Taufique & Vaithianathan, 2018).…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Marketing literature argues that consumer attitude is one of the main determinants of consumer’s purchase intention and behaviour (Ghose & Chandra, 2020; Hauser et al, 2013; Krystallis et al, 2012; Malik & Singhal, 2017; Mann, & Kaur, 2019; Stöckigt et al, 2019; Wu & Chen, 2014). However, consumer attitude is a very subjective concept which varies the nature of the product and product set.…”
Section: Hypothesis Developmentmentioning
confidence: 99%
“…Past studies have also reported that attitude is significantly positively related to green purchase intentions (Chaudhary and Bisai, 2018;Wang et al, 2020;Verma et al, 2019), actual green behavior (Tan et al, 2017;Sia and Jose, 2019;Khan et al, 2020), willingness to behave environmentally (Malik and Singhal, 2017), and environment responsible purchase intention (Kumar et al, 2021). Hence, it is hypothesized that:…”
Section: Attitudementioning
confidence: 98%
“…Kautish and Dash (2017) in favor of this view posited environmental knowledge as a significant driver of "good" and "rational" choice-making among consumers. Previous studies have placed consumer knowledge as a central element in enhancing pro-environmental consumer behavior (Bhuian et al, 2018), green purchase tendencies, intentions (G€ oçer and Oflaç, 2017;Waris and Hameed, 2020), willingness to behave environmentally (Malik and Singhal, 2017), environmentally conscious consumer behavior (Kautish and Sharma, 2020), green consumer behavior (Khan et al, 2020) and environment responsibility (Pawaskar et al, 2018). Hence, it is hypothesized that H1.…”
Section: Environmental Responsibility Among Consumersmentioning
confidence: 99%